MAPPING CENTRAL BANK DIGITAL CURRENCY LITERATURE: LESSONS FOR GOVERNMENTS AND RESEARCH - Riani, Ririn; Akbar, Nashr (Bank Indonesia, 2024)
CBDC has gained popularity in many countries as a result of technological development. Central banks in a number of nations have been experimenting, piloting, launching, and promoting CBDC. Therefore, this study maps CBDC-related literature using a bibliometric approach and content analysis of the Scopus database. The Biblioshiny R Package was used in this study to analyse 190 documents with the keywords “central bank digital currency”. The analysis focuses on the main information about all documents, analysis of scientific production by areas (journals, authors, and countries), document and keyword analysis, and policy recommendations from the previous literature. The results show that CBDCs have had profound effects on monetary and payment systems, and their development could set the stage for a global central bank. The review also addresses the motivations and advantages of issuing a CBDC, including increasing financial inclusion, enhancing monetary policy, andpromoting efficient digital payments. The analysis also reveals that numerous central banks are investigating the possibility of issuing CBDCs due to the numerous advantages of this form of money. There is a lot of potential for theoretical expansion, contextual coverage, and methodological contributions. Furthermore, some policy recommendations from previous literature and directions for future studies are provided in this study.